Induction of a pharmacoeconomics course in pharmacy curriculum: preliminary findings from the final year cohort - Alshami, Abdulkareem Mohammed; Jamshed, Shazia Qasim; Shafie, Asrul Akmal (Malaysian Pharmaceutical Society, 2015)
Objectives: Escalating healthcare costs and pharmaceutical spending continue to evolve rapidly. With the aim of curtailing the cost of treatment, there is an increased demand of understanding and applying the pharmacoeconomics principles. In the backdrop of this we developed and implement a 2-credit hour pharmacoeconomics module which constitutes didactic lectures, literature review workshops, and assignments in our final year cohort. This study is aimed to assess the views and attitudes of final year pharmacy students about the concepts and application of Pharmacoeconomics. Method: A cross-sectional survey was performed among a final year cohort of 99 students in October 2013. A pre-validated, 15-item, questionnaire was used to assess the students views and attitudes towards this course. Results: All the students of final year cohort (n= 28 males; n= 71 females) responded the survey. Three-fourth of the students (n= 76; 76.6 %) strongly agreed to have little knowledge of pharmacoeconomics before this course. Majority of the students (n=65; 65.5%) strongly agreed that the class exercises helped them better to understand the course material. A large majority (n=61; 61.61%) strongly disagreed to evaluate the pharmacoeconomics literature confidently. Majority (n=62; 62.62%) expressed their intention to apply pharmacoeconomics principles in their professional practice. Majority (n=75; 75.75 %) expressed their desire work as a hospital pharmacist. Conclusion: Students expressed to learn well about the basic concepts of pharmacoeconomics principles and expressed positive attitude towards the learning of application of pharmacoeconomics principles. The introduction of pharmacoeconomics principles is recommended to be included in the initial pharmacy years.